Similar pattern of atrophy in early‐ and late‐onset Alzheimer's disease. Issue 1 (1st March 2018) - Eckerström, Carl; Klasson, Niklas; Olsson, Erik; Selnes, Per; Rolstad, Sindre; Wallin, Anders
Abstract: Introduction: Previous research on structural changes in early‐onset Alzheimer's disease (EOAD) and late‐onset Alzheimer's disease (LOAD) have reported inconsistent findings. Methods: In the present substudy of the Gothenburg MCI study, 1.5 T scans were used to estimate lobar and hippocampal volumes using FreeSurfer. Study participants (N = 145) included 63 patients with AD, (24 patients with EOAD [aged ≤65 years], 39 patients with LOAD [aged >65 years]), 25 healthy controls aged ≤65 years, and 57 healthy controls aged >65 years. Results: Hippocampal atrophy is the most prominent feature of both EOAD and LOAD compared with controls. Direct comparison between EOAD and LOAD showed that the differences between the groups did not remain after correcting for age. Discussion: Structurally, EOAD and LOAD does not seem to be different nosological entities. The difference in brain volumes between the groups compared with controls is likely due to age‐related atrophy. Highlights: Hippocampal atrophy is the most prominent feature of both early‐ and late‐onset AD. No structural difference between early‐ and late‐onset AD after adjusting for age. Early‐ and late‐onset AD exhibits a similar pattern of atrophy.